“Expert persuasion” can decrease willingness to pay for sugar-containing food - Ntoumanis, Ioannis; Panidi, Ksenia; Grebenschikova, Yaroslava; Shestakova, Anna N.; Kosonogov, Vladimir; Jääskeläinen, Iiro P.; Kadieva, Dzerassa; Baran, Sofia; Klucharev, Vasily (Frontiers in Nutrition, 2022)
Recent studies have revealed types of eating nudges that can steer consumers towards choosing healthier options. However, most of the previously studied interventions target individual decisions and are not directed to changing consumers’ underlying perception of unhealthy food. Here, we investigate how a healthy eating call - first-person narrative by a health expert - affects individuals’ willingness to pay (WTP) for sugar-free and sugar-containing food products. Participants performed two blocks of a bidding task, in which they had to bid on sweets labeled either as “sugar-free” or as “sugar-containing”. In-between the two blocks, half of the participants listened to a narrative by a dietary specialist emphasizing the health risks of sugar consumption, whereas the remaining participants listened to a control narrative irrelevant to food choices. We demonstrate that the health expert’s narrative decreased individuals’ WTP for sugar-containing food, but did not modulate their WTP for sugar-free food. Overall, our findings confirm that consumers may conform to healthy eating calls by rather devaluating unhealthy food products than by increasing the value of healthy ones. This paves the way for an avenue of innovative marketing strategies to support individuals in their food choices.